HOMBO BATU THE TRADITION OF SOUTH NIAS THAT TEACHES COURAGE AND COOPERATION - Harefa, Darmawan (Universitas Nias Raya, 2025)
Hombo Batu is a traditional custom that has been practiced for a long time in South Nias. It not only serves as a form of entertainment but also teaches values of courage and cooperation within the community. This tradition involves two teams facing each other, aiming to defeat the opponent through physical strength and strategy. This study aims to explore how Hombo Batu, as a cultural heritage, teaches the younger generation about the importance of courage, cooperation, and solidarity. The research method used is a field study with a qualitative approach, which includes direct observation, interviews, and literature review to collect data on the implementation and meaning behind this tradition. The research findings indicate that Hombo Batu is more than just a physical game; it also serves as a profound character-building tool. Courage in facing challenges and cooperation among team members are key aspects that can be applied to the social life of the Nias community. Furthermore, Hombo Batu also plays a role in preserving the cultural identity of the Nias people amidst the tides of globalization. This study is expected to enrich the understanding of the importance of preserving local traditions as a tool for character education in the modern era.